Cytogenetic screening of cattle and buffalo breeding bulls - Youdhveer Singh; AS Yadav; SK Niranjan; B Prakash (Journal of Livestock Biodiversity, 2025)
Chromosomal abnormalities cause a drop in reproductive performance or even complete infertility/sterility in the carrier animals. Present investigation was undertaken to detect chromosomal abnormality, if any, in 155 breeding bulls of exotic (Bos taurus, 2n=60), indigenous (Bos indicus, 2n=60) cattle, their crossbreeds and Murrah buffalo (Bubalus bubalis, 2n = 50) maintained by various organizations. Mitotic chromosome spreads were prepared and analysed from cultured lymphocytes of 155 breeding bulls of different indicus, exotic and crossbred cattle (Holstein Friesian, Jersey, Red Sindhi and Sahiwal) and 41 Murrah buffalo bulls reserved for breeding and maintained at different stations of State Livestock Development Boards from the state of Haryana, Punjab, Uttrakhand, Jammu and Kashmir, Rajasthan and Assam. Giemsa staining of chromosomes revealed that 98.2% cattle bulls possessed normal chromosome complements. One Holstein-Friesian and one HF crossbred bulls were found to be sex chromosome chimeric (60, XX/60, XY). No chromosomal abnormality could be detected in any of the Murrah buffalo bulls studied. Such regular cytogenetic screening will not only reduce the occurrence of chromosomal abnormalities in dairy animal population but also will save the time and cost of rearing the abnormal animals.